41-LB: Changes in Circulating Metabolites, Including Butyrate, Points to Underlying Mechanism of a Probiotic Intervention That Improves Postprandial Hyperglycemia in Subjects with Type 2 Diabetes - MCMURDIE, PAUL; STOEVA, MAGDALENA K.; NEMCHEK, MADELEINE; TYAGI, SURABHI; GINES, JESSICA; EID, JOHN; KOLTERMAN, ORVILLE G. (Diabetes (New York, N.Y.), 2021)
Studies in type 2 diabetes (T2D) rodent models suggest the potential for individual microbial taxa in the human gut to improve or worsen metabolic disease via specific metabolites (signals) in hepatic or general circulation. We previously reported significant improvement in postprandial glucose control in T2D subjects following ingestion of a 5-strain novel probiotic formulation (INT) in a placebo (PBO) controlled setting. (DOI:10.1136/bmjdrc-2020-001319) Here we report measurements of fecal and fasting circulating plasma metabolites, implicated as mediators of microbiome effects, collected before and after the 12-week intervention. Consistent with the hypothesized benefits of increased colonic production of butyrate, plasma butyrate increased in INT but not PBO (within group, concentration increase = 0.15 µM, p = 0.007; between group, p = 0.11), but not acetate nor propionate, paralleling changes in subject stool and production by in vitro culture. We detected changes consistent with enhanced fatty acid oxidation in INT relative to placebo, especially a decrease in medium chain fatty acids, their carnitinylates, and a decrease in bilirubin degradation byproducts. We also detected increases in certain bile acids, especially ursodeoxycholic acid (UDCA). In vitro monoculture supernatant showed that the formulation’s C. butyricum strain specifically and efficiently synthesizes UDCA during butyrogenic growth in rich media amended with the primary bile acid chenodeoxycholic acid. Untargeted data also uncovered previously undocumented use of sulfonylurea (SFU), accounting for 6 out of 7 subjects with A1c non-response in the INT group. To our knowledge, this is the first description of an increase in circulating butyrate and UDCA due solely to a bacterial probiotic intervention in humans with T2D, and may help explain the observed improvement in postprandial glucose control.